“Hear Ye All, These Walls Really Talk!” Exploring he Communicative Functions of College Students’ Graffiti on School Campus Wall - Mangila, Benjamin; Avenido, Venus (ETERNAL (English, Teaching, Learning and Research Journal), 2023)
Although there have been extensive studies on graffiti in various disciplines and contexts worldwide, only a few contemporary studies have been conducted on the classroom walls in higher education milieus. As such, this study explored the communicative functions of students’ graffiti-writings found on the classroom walls of a Philippine state college. Utilizing Content Analysis (CA), the results clearly revealed that graffiti-writings had been utilized by college students as their unique means of communicating their personal thoughts and feelings, as well as their antagonistic attitudes toward other individuals, groups, and even institutions which they could not express openly in public. Graffiti-writings had also been used by college students to seek glorification among themselves, to show their intelligence or wittiness, and to express resentment or hatred especially to the members of the LGBTQIA+ society. Indeed, graffiti-writings performed a multiplicity of communicative functions, having anonymity as a very powerful and useful tool used by college students not only in concealing their personal identities and advancing their causes and rights, but also in effectively protecting themselves from the harsh consequences which they might face when caught doing this highly forbidden act.